Mētis and violence in Machiavellian political theory - Queiroz, Regina (2017)
The quest for winning and preserving politicalpower in Machiavelli’s The Prince is led by the bellicose versionof the pre-classical and mythological concept of metisor cunning rationality. In opposition to a domestic version ofcunning rationality, understood as the rationality of the weak,Machiavellian mētis is a prudential and deceptive rationalityof the strong. Bellicose cunning rationality does not, however,prevent the prince from falling into the hubris of violence,and does not avoid undermining cunning rationality itself.Our article evaluates and circumscribes the contribution, aswell as the theoretical and practical limits of the Machiavellianbellicose cunning rationality.